Two-row Motorized Paddy Weeder for Irrigated and Rainfed Lowland Systems in Eastern Africa - CGIAR Research Program on Rice (2021)
Locally adapted weeders were developed in collaboration with private fabricators and tested with farmers in 2016 and 2017 in Tanzania. The adapted weeders developed in Tanzania were imported to other countries for local adaptation. Testing and adaptation being completed in Kenya, Madagascar and Uganda in 2020-2021.